Poly aromatic hydrocarbons degradation by lignin peroxidase produced from local isolate Aspergillus terreus SG777 - Imran, Sahar Ghazi; Razuqi, Nada S.; Aziz, Ghazi M. (Journal of Petroleum Research and Studies, 2018)
Lignin peroxidase produced from A. terreus SG777 precipitated with 80% ammonium sulfate saturation then desalting by dialysis against Tris buffer solution and partially purified by ion exchange chromatography using DEAE- cellulose.The specific activity reached 56.67U/mg with purification fold was 5.4 times and 13.7% recovery. The optimum pH for activity and stability was (3). The maximum activity was observed at 40°C and the enzyme maintained the activity when it was incubated at (25-35)˚C. Degradation of poly aromatic hydrocarbons when incubated with 65.51 U/ml lignin peroxidase at (40°C) for 4 hr compared with the Refinery treatment. Results showed (97.54%) removal efficiency of Di benzo (a, h) anthrancene by lignin peroxidase, while only (54.37%) was treated by Refinery treatment. Flourene and anthrancene degradation (95.98%) and (83.51%) respectively, while the flourene and anthrancene degradation treated by Refinery treatment only 84.51% and (46.83%) respectively. The aim of this study was degradation of poly aromatic hydrocarbons by using partial purification lignin peroxidase.